Prehospital critical care is associated with increased survival in adult trauma patients in Scotland. Issue 3 (20th January 2020) - Maddock, Alistair; Corfield, Alasdair R; Donald, Michael J; Lyon, Richard M; Sinclair, Neil; Fitzpatrick, David; Carr, David; Hearns, Stephen
Abstract : Background: Scotland has three prehospital critical care teams (PHCCTs) providing enhanced care support to a usually paramedic-delivered ambulance service. The effect of the PHCCTs on patient survival following trauma in Scotland is not currently known nationally. Methods: National registry-based retrospective cohort study using 2011–2016 data from the Scottish Trauma Audit Group. 30-day mortality was compared between groups after multivariate analysis to account for confounding variables. Results: Our data set comprised 17 157 patients, with a mean age of 54.7 years and 8206 (57.5%) of male gender. 2877 patients in the registry were excluded due to incomplete data on their level of prehospital care, leaving an eligible group of 14 280. 13 504 injured adults who received care from ambulance clinicians (paramedics or technicians) were compared with 776 whose care included input from a PHCCT. The median Injury Severity Score (ISS) across all eligible patients was 9; 3076 patients (21.5%) met the ISS>15 criterion for major trauma. Patients in the PHCCT cohort were statistically significantly (all p<0.01) more likely to be male; be transported to a prospective Major Trauma Centre; have suffered major trauma; have suffered a severe head injury; be transported by air and be intubated prior to arrival in hospital. Following multivariate analysis, the OR for 30-day mortality for patients seen by a PHCCT was 0.56 (95% CI 0.36 to 0.86, p=0.01). Conclusion: Prehospital care provided by a physician-led critical care team was associated with an increased chance of survival at 30 days when compared with care provided by ambulance clinicians.